Permintaan, Penawaran Dan Keseimbangan Harga Dalam Prespektif Ekonomi Mikro Islam - M. Dliyaul Muflihin (JES (Jurnal Ekonomi Syariah), 2019)
In general, we believe that humans are social creatures with the need to complement each other’s lives, with each other's unlimited desires. While a Muslim is only allowed to consume halal and good. In Islamic teachings, illicit goods for consumption are not allowed to be made the basis of buying and selling or other transactions. In the demand and supply curves of Islam there are restrictions that must be done as a Muslim which is used as a basis for economic behavior. These restrictions are prohibited from making mafsadah, gharat, maisir, usury. This paper will answer the question how is the demand, supply and price balance in the perspective of Islamic microeconomics. The results of research shows that the concept of demand and supply in Islamic Islam aims to obtain prosperity or victory in the hereafter (falah) as a derivation of the belief that there is an eternal life after death, namely the after life, so that the existing budget must be set aside as provisions for the afterlife, such as alms and zakat. This means that there is a significant difference between conventional demand theory and Islamic demand theory. In conventional economics, consumers and producers have motivations that are dominated by the values of satisfaction, but in Islamic economics emphasizes only the level of need. The Islamic price balance mechanism in Islam is determined by the balance between demand and supply. This means that the price balance in the market is formed naturally, not because there is interference from the capitalist who can distort the market. This shows that the price regulation is left to the natural impersonal market mechanism. Keywords: Demand, Supply, Islamic perspective